PENGARUH KEPUASAN KERJA, MOTIVASI, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi Kasus pada Karyawan Giant Ekspres PT. Hero Supermarket Tbk. Cabang Dinoyo) - Faiqotul Khumaidah; Abdul Qodir Djaelani; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to examine and analyze the influence of job satisfaction, motivation and leadership style on employee performance of PT. Hero Supermarket Tbk. Dinoyo branch either partially or together. The population and sample are all 41 employees. Data collection through questionnaire distribution. Data analysis in this research using SPSS version 14. Sampling technique using census method and data testing technique used in this research include validity test, reliability test, classical assumption test and multiple linear regression analysis, and hypothesis testing research.The results showed that partially motivation does not significantly affect employee performance while job satisfaction and leadership style significantly influence employee performance. Together shows that job satisfaction, motivation and leadership style significantly influence employee performance.Keywords: Job Satisfaction, Motivation, Leadership Style and Employee Performance.